LncRNA‐SNHG15 enhances cell proliferation in colorectal cancer by inhibiting miR‐338‐3p. (3rd April 2019) - Li, Min; Bian, Zehua; Jin, Guoying; Zhang, Jia; Yao, Surui; Feng, Yuyang; Wang, Xue; Yin, Yuan; Fei, Bojian; You, Qingjun; Huang, Zhaohui
Abstract: The incidence and death rate of colorectal cancer (CRC) is very high, which brings great need to understand the early molecular events of CRC. These studies demonstrate that long noncoding RNA (lncRNA) plays an important role in the occurrence and development of human cancer. Small nucleolar RNA host gene 15 (SNHG15) was recently identified as a cancer‐related lncRNA. In this study, we aimed to evaluate the function and mechanism of SNHG15 in CRC. The expression of SNHG15 was detected by quantitative RT‐PCR (qRT‐PCR) in CRC tissues and matched noncancerous tissues (NCTs). CCK‐8 assay, colony formation assay, flow cytometric analysis, and nude mouse xenograft mode were used to examine the tumor‐promoting function of SNHG15 in vitro and in vivo. The binding relationship between SNHG15, miR‐338‐3p and the target genes of miR‐338‐3p were screened and identified by databases, qRT‐PCR, dual luciferase reporter assay and western blot. Our results showed that SNHG15 was up‐regulated in CRC tissues compared with paired NCTs ( P < 0.0001). High level of SNHG15 expression predicted poor prognosis of CRC ( P = 0.0051). SNHG15 overexpression could promote cell proliferation and inhibit cell apoptosis. Animal experiments showed that up‐regulation of SNHG15 promoted tumor growth in vivo. The results of mechanism experiments showed that SNHG15 could bind to miR‐338‐3p and block its inhibition on the expression and activity of FOS or RAB14. In conclusion SNHG15 promotes cell proliferation through SNHG15/miR‐338‐3p/FOS‐RAB14 axis in CRC. Abstract : Overexpression of SNHG15 could promote cell proliferation in vitro and in vivo. Mechanism experiments showed that SNHG15 could bind to miR‐338‐3p and block its inhibition on the expression and activity of FOS or RAB14. In conclusion SNHG15 promotes cell proliferation through SNHG15/miR‐338‐3p/FOS (RAB14) axis in CRC.